Mandibular Advancement Means Lower Facial Enlargement: A 2-Dimensional and 3-Dimensional Analysis - Sigaux, Nicolas; Mojallal, Ali; Breton, Pierre; Giai, Joris; Louvrier, Aurélien; Bouletreau, Pierre (Journal of oral and maxillofacial surgery, 2018)
Bilateral sagittal split osteotomy (BSSO) is frequently used to treat Class II malocclusion for functional and esthetic purposes, with expected changes in the profile. The goal of this study was to assess transversal changes in mandibular advancement by comparing 3-dimensional (3D) photogrammetric modifications and 2-dimensional (2D) radiographic enlargement. A cohort study was conducted of patients who underwent an isolated advancement BSSO (Obwegeser-Dal Pont II type) for a Class II malocclusion. All patients had 3D photogrammetric and 2D radiographic evaluations before and after surgery. Frontal cephalograms were used to measure the evolution of bigonial distance (BGD) and 3D photographs were used to measure the evolution of cutaneous BGD (CBGD). Fourteen patients were included. Mean mandibular advancement was 6 mm. BGD (+6.1 mm; P < 10 ) and CBGD (+4.2 mm; P = .0017) were significantly increased. The mean ratio of soft tissue response to transversal skeletal changes was 0.81. This 2D and 3D analysis of transversal modifications shows that advancement with the BSSO is responsible for marked lower third facial enlargement. This parameter must be taken into account during the preoperative esthetic assessment to ensure the provision of pertinent information to the patient and the consideration of complementary surgical correction.